1989
DOI: 10.1111/j.1399-3011.1989.tb00701.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological activities of oxytocin and lysine vasopressin analogs containing glutamic acid γ‐hydrazide in position 4

Abstract: Solution methods, using N-hydroxysuccinimide esters, were used to synthesize [GIu(NHNH,)~] oxytocin and [GIu(NHNH,)~, Lys'] vasopressin. In these analogs of neurohypophyseal hormones, the side-chain carboxamide function of a glutamine residue is formally replaced by a hydrazide group at position 4. The hormone analogs were assayed for uterototonic activity, milk ejection activity, antidiuretic activity, and rat pressor activity. The specific biological activities of the oxytocin and vasopressin analogs were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…The slope of this linear regression gives the k scavenger = 7 × 10 7 M −1 s −1 , i.e., the k value for the oxidation of diethyl selenodiglycolate by HOCl. This constant was similar to the ones found for the reaction of HOCl with other seleno derivatives and with glutathione [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] (1.1 × 10 8 M −1 s −1 ), showing that diethyl selenodiglycolate might be a competitive antioxidant in biological systems to scavenger HOCl and to maintain the levels of untouched glutathione.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The slope of this linear regression gives the k scavenger = 7 × 10 7 M −1 s −1 , i.e., the k value for the oxidation of diethyl selenodiglycolate by HOCl. This constant was similar to the ones found for the reaction of HOCl with other seleno derivatives and with glutathione [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] (1.1 × 10 8 M −1 s −1 ), showing that diethyl selenodiglycolate might be a competitive antioxidant in biological systems to scavenger HOCl and to maintain the levels of untouched glutathione.…”
Section: Resultssupporting
confidence: 78%
“…H NMR (200 MHz, DMSO-d 6 , deuterated dimethyl sulfoxide) d 12.7 (ls, 1H), 8.00-7.30 (m, 8H), 4.44-3.99 (m, 4H), 2.07 (s, 3H), 1.90 (m, 2H); 13 C NMR (50 MHz, DMSO-d 6 ) d 174.18, 156.64, 144.25, 144.17, 141.14, 128.05, 127.47, 125.66, 120.50, 66.01, 53.09, 47.09, 30.75, 30.26, 14.91 (SI section) 25. …”
mentioning
confidence: 99%
“…14 An earlier publication by Gazis et al reported an elaborate procedure for solution-phase coupling of α-Boc-δ-Cbz-protected glutamic acid hydrazide (low-temperature activation with isobutyl chloroformate) even though standard NHS-ester-based activations were the norm for other coupling reactions in their work. 9 Some other reports either omit the description of how these peptides were synthesized or omit reporting yields.…”
Section: Resultsmentioning
confidence: 99%
“…Some, but not many examples of glutamyl hydrazide containing peptides have been reported. An earlier report by Gazis et al 9 studied the biochemical impact of replacing the C(O)NH 2 side chain of Gln residues in two peptide hormones with C(O)NHNH 2 . Quartararo and co-workers 10 used the hydrazide group as a nucleophile to connect peptides to other moieties via amide linkages.…”
Section: Introductionmentioning
confidence: 99%